2013
DOI: 10.1007/s00436-013-3277-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Imidacloprid 10 % / Flumethrin 4.5 % Collar (Seresto®, Bayer) for Preventing the Transmission of Cytauxzoon felis to Domestic Cats by Amblyomma americanum

Abstract: Infection of Cytauxzoon felis in domestic cats produces a severe disease characterised by fever, lethargy, inappetence, anorexia, depression, dehydration, icterus and often death. Transmission of C. felis to cats is dependent on being fed upon by infected Amblyomma americanum (lone star ticks). The purpose of the present study was to determine if application of a 10 % imidacloprid/4.5 % flumethrin collar (Seresto®, Bayer) on cats prevents transmission of C. felis by repelling ticks. Twenty cats were randomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 27 publications
0
38
0
4
Order By: Relevance
“…Recent research supports the conclusions by the CVBD forum and the ACVIM consensus statement that products with repellent properties are important to aid in the prevention of vector-borne disease transmission. Specifically, Seresto ® has been shown to Fourie et al 2013a;Reichard et al 2013;Stanneck et al 2012). Seresto ® also aided in the prevention of Bartonella helselae transmission by C. felis and Leishmania infantum transmission by sand flies (Brianti et al 2014;Lappin et al 2013;Otranto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research supports the conclusions by the CVBD forum and the ACVIM consensus statement that products with repellent properties are important to aid in the prevention of vector-borne disease transmission. Specifically, Seresto ® has been shown to Fourie et al 2013a;Reichard et al 2013;Stanneck et al 2012). Seresto ® also aided in the prevention of Bartonella helselae transmission by C. felis and Leishmania infantum transmission by sand flies (Brianti et al 2014;Lappin et al 2013;Otranto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Using a product with repellent properties, such as Seresto ® , can inhibit ticks from attaching and feeding, therefore aiding in the prevention of disease transmission. While this was not a disease transmission study, several studies have successfully confirmed the ability of Seresto ® to help prevent the transmission of disease-causing organisms to dogs and cats including: Ehrlichia canis, Babesia canis, Babesia vogeli, Anaplasma platys, and Cytauxzoon felis (Dantas-Torres et al 2013;Fourie et al 2013a;Reichard et al 2013;Stanneck and Fourie 2013). A product that offers repellency and/or a rapid speed of kill may also reduce the likelihood of transmission of pathogens between ticks.…”
Section: S104mentioning
confidence: 99%
“…Recently introduced slow-release matrix collars containing imidacloprid 10 % (w/w) /flumethrin 4.5 % (w/w) (Seresto ® , Bayer) have proven to be highly effective for up to 8 months against infestations of ixodid ticks and fleas on cats (Stanneck et al 2012a, Stanneck et al 2012b. Its acaricidal active flumethrin is the first on the market to provide acaricidal (killing) and repellent (anti-feeding) efficacy for the treatment and prevention of tick infestations on cats, thus preventing repelled parasites from taking a blood meal and thereby indirectly aids in the reduction of the risk of vectorborne disease transmission, as demonstrated for the prevention of transmission of Cytauxzoon felis by Amblyomma americanum ticks (Reichard et al 2013). In addition, an effective repellent or speed of kill effect against ticks (in particular I. ricinus) is also evident for 34 weeks after application of the collars.…”
Section: Introductionmentioning
confidence: 99%